Diseño de una máquina para la fabricación de briquetas de posos de Café (2020)
The importance of developing the project lies in the use of coffee grounds to reduce the environmental impact that the release of methane would generate due to the decomposition of these residues. Additionally, it would provide any company that is engaged in the manufacture of briquettes, a new alternative design of a machine that is capable of making briquettes for possible construction and implementation. The problem originates due to the high consumption of coffee, the preparation of this product generates a type of residue commonly known as borra, husk, cuncho, poso or gravel, this is the sediment that leaves the coffee in a filter after being prepared and strained